Additives for plastics handbooks - Murphy, John, 1934 May 23- (Elsevier Science Ltd., 2001)
Both technically and economically, additives form a large and increasingly significant part of the polymer industry, both plastics and elastomers. Since the first edition of this book was published, there have been wide-ranging developments, covering chemistry and formulation of new and more efficient additive systems and the safer use of additives, both by processors in the factory and, in the wider field, as they affect the general public. This new edition follows the successful formula of its predecessor, it provides a comprehensive view of all types of additives, concentrating mainly on their technical aspects (chemistry/formulation, structure, function, main applications) with notes on the commercial background of each. The field has been expanded to include any substance that is added to a polymer to improve its use, so including reinforcing materials (such as glass fibre), carbon black and titanium dioxide. This is a book which has been planned for ease of use and the information is presented in a way which is appropriate to the users' needs.